The Home, Pension Savings, and Risk Aversion: Intentions of the Defined Contribution Pension Plan Participants of a London-based Investment Bank at the Peak of the Bubble. - Clark, G; Almond, S; Strauss, K (School of Geography and Environment (University of Oxford), 2010)
In the lead-up to the peak of the financial bubble (and before the onset of the global financial crisis), UK newspapers regularly touted property as a ready-made alternative to private pensions. In this paper we explore the importance of the property in which respondents live for their retirement savings strategies. Based upon a unique survey of over 2,400 participants in the defined contribution pension scheme of a London-based international bank, we assess the statistical significance of respondents' socio-economic status and risk preference in predicting the significance or otherwise of their home for retirement saving. Relatively few respondents indicated that they were likely to rely on their hom. Those that indicated reliance were relatively older, higher paid, and married employees. The paper concludes with implications for understanding the connection between savings behaviour and housing before and after the global financial crisis.